Identificación las principales plagas y enfermedades que inciden en el cultivo de limón (Citrus) localizado en la parroquia de Chaltura, Antonio Ante, provincia de Imbabura - Pita Vásquez, Miguel Ángel (2019)
SUMMARY This research was made by acknowledge over growing lemon’s pets and the variety of diseases, it has attacked to Chaltura city into Imbabura´s County, this growing´s investigation was analyzed with different data in which, they were gotten them the primary pets were aphids) con el 60% mite con el 60% and the major diseases were fumagina (capnodium ) 40% y gummosis (Phythopthora cinnamomi) 10% it is recommended to take a remarkable pest´control and diseases ‘control and even to take in main the lifecycle. Keywords: Lemon, incidence, pests, control